Improving students’ critical thinking skills through the problem based learning (pbl) model in islamic religious education at smpit permata - Sinta Ma’sumah; Nur Wiji Sholikin (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) learning model in improving critical thinking skills in Islamic Religious Education (PAI) subjects at SMPIT Permata in Probolinggo City. The method applied is quantitative, namely designed using a quasi-experimental design. The subjects consisted of 33 seventh-grade students divided into an experimental class (21 students) and a control class (12 students). The instruments were tests (pretest and posttest), interview guidelines, and documentation of learning outcomes. The results of the analysis showed a significant increase in the average posttest score of the experimental class was 90.05 (very high category) which increased to 28.43 points (46.1%) compared to the pretest. The control class showed an average increase of 19.5 points (31.7%) with a posttest score of 81.08 (high category). Qualitative data supported the findings through increased active participation, analytical skills, and contextual relevance during learning. The application of the PBL model has been proven effective in developing critical thinking skills in Islamic Religious Education learning at the junior high school level.